Donor CD4 T Cell Diversity Determines Virus Reactivation in Patients After HLA‐Matched Allogeneic Stem Cell Transplantation. Issue 8 (14th April 2015) - Ritter, J.; Seitz, V.; Balzer, H.; Gary, R.; Lenze, D.; Moi, S.; Pasemann, S.; Seegebarth, A.; Wurdack, M.; Hennig, S.; Gerbitz, A.; Hummel, M.
<x xml:space="preserve">Abstract</x> Delayed reconstitution of the T cell compartment in recipients of allogeneic stem cell grafts is associated with an increase of reactivation of latent viruses. Thereby, the transplanted T cell repertoire appears to be one of the factors that affect T cell reconstitution. Therefore, we studied the T cell receptor beta (TCRβ) gene rearrangements of flow cytometry–sorted CD4+ and CD8+ T cells from the peripheral blood of 23 allogeneic donors before G‐CSF administration and on the day of apheresis. For this purpose, TCRβ rearrangements were amplified by multiplex PCR followed by high‐throughput amplicon sequencing. Overall, CD4+ T cells displayed a significantly higher TCRβ diversity compared to CD8+ T cells irrespective of G‐CSF administration. In line, no significant impact of G‐CSF treatment on the TCR Vβ repertoire usage was found. However, correlation of the donor T cell repertoire with clinical outcomes of the recipient revealed that a higher CD4+ TCRβ diversity after G‐CSF treatment is associated with lower reactivation of cytomegalovirus and Epstein–Barr virus. By contrast, no protecting correlation was observed for CD8+ T cells. In essence, our deep TCRβ analysis identifies the importance of the CD4+ T cell compartment for the control of latent viruses after allogeneic stem cell transplantation.